Art and architecture of Ireland : Volume I: Medieval c. 400-c. 1600 - Moss, Rachel Laura; Moss, Rachel Laura (Royal Irish Academy, 2015)
Introduction -- Influences an impacts -- Movements, motifs and meanings -- Materials and methods -- Monuments of Christianity -- Art of worship and devotion -- Settlement and society -- Art and identity -- Patrons and practitioners -- Select handlist of artists and craftsmen -- Records of art and architectural patronage at Athenry Friary -- The O'Tunney Atelier, their clients and distribution of their work -- Glossary.